Constraints Faced by Deoni Cattle Rearers and Non-descriptive Cattle Rearers in the Adoption of Management Practices - B. L. Pisure , Deshmukh P. R; Thombre B. M (Indian Journal of Extension Education, 2016)
The present study was conducted purposively in Latur district of the Marathwada region of Maharashtra state. 120 respondents of Deoni cattle and 120 respondents of Non-descriptive cattle from Latur district were selected. Thus, there were a total of 240 respondents selected for the research study. Ex-post facto research design was adopted in this study. The data were collected with the help of pretested interview schedule. It was found that, deoni cattle rearers were lack of knowledge about management of pregnant cow and newly born calf was the most important constraint (91.67 %) in the management of pregnant cow and newly born calf followed by lack of knowledge about improved dairy production practices (90.00 %) and lack of contact between dairy farmers and veterinarians (76.00 %) was reported as secondary constraints reported by deoni cattle rearers. Inadequate knowledge about breeding practices (94.17 %). While nondescriptive cattle rearers seeking knowledge about improved dairy production practices (93.33 %) was reported as major problem followed by lack of knowledge about management of pregnant cow and newly born calf (92.50 %) and lack of contact between dairy farmers and veterinarians (76.67 %). However, it was reported that inadequate knowledge about breeding practices (97.50 %) was the major constraint in adoption of breeding management practices.